Sustainable settlement development - Assessing the effects of state measuresin scenario analysis - Martin Distelkamp; Philip Ulrich (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2009)
The underlying research project was sponsored by the German Federal Ministry of Education and Research (BMBF) in the funding programme Research for the Reduction of Land Consumption and for Sustainable Land Management (REFINA). REFINA is implemented by the BMBF in cooperation with the Federal Ministry of Transport, Building and Urban Affairs (BMVBS) and the Federal Ministry for the Environment, Nature Conservation and Nuclear Safety (BMU). Since 2006, the projects funded have developed innovative concepts for reducing the rate of land consumption and for encouraging sustainable land management.
Keywords: O13; R14; 330; 15th International Sustainable Development Conference